Design and Build Basic Electronics Trainer as a Practicum Teaching Aid at the Electronics Engineering Laboratory, Universitas Pembangunan Panca Budi, Medan - Sylvia Larasati; Amani Darma Tarigan; Yofie Adinata (Yayasan Sinergi Multidimensi Kreatif, 2024)
This research aims to design and build a basic electronics trainer as a practicum teaching aid at the Electronics Engineering Laboratory, Panca Budi Development University, Medan. The problem faced in the learning process in the industrial automation course is the lack of supporting learning media, so that students have difficulty understanding the theory and its application, especially in the assembly and programming of basic electronic systems. Based on the results of observations, interviews, and questionnaire distribution, it is known that the lack of practicum teaching aids affects the effectiveness of learning.This research method includes the stages of hardware and software design, the manufacture of trainer kits, and the testing of tool functionality. The designed trainer is expected to facilitate students in understanding the basic principles of electronics through interactive and applicable practicums. The use of this trainer aims to provide convenience in understanding theory, as well as improve students' practical skills in assembling and operating basic electronic systems.The result of this study is a basic electronics trainer that can be used as an effective, efficient, and easy-to-operate learning medium. This trainer also makes a significant contribution to increasing student motivation and understanding of the material taught. With this tool, students are expected to be more involved in the learning process, both theoretically and practically, and ready to face challenges in the real industrial world.